ANALISIS PERANAN SEKTOR PERTANIAN DAN PENGEMBANGANNYA DI KABUPATEN BURU - Maimuna Talaohu; Izaac Tonny Matitaputty; Maryam Sangadji (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2019)
The agricultural sector as one of the economic sectors is a very potential sector in contributing to regional economic development. This research was conducted to determine the contribution of agricultural secrtor to GDRP, the position of the food crop, horticulture, plantation, and livestock sub sector and its development strategy in Buru Regency. The study used contribution analysis method, analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ) and SWOT analysis. The results of the study showed that the agricultural sector contributed greatly to Buru Regency GDRP with its four sub sectors being the base sub-sector and the basis for the future was livestock sub-sector. The strategy undertaken in developing the four agricultural sub sectors was an agressive strategy that uses power to utilize existing opportunities.